TECHNOLOGY, COLLABORATION, AND HUMANISTIC VALUES: A TRIAD FOR REVOLUTIONIZING MEDICAL EDUCATION - Khan, Muhammad Junaid (Journal of Ayub Medical College Abbottabad, 2024)
Medical education must be revolutionized in today's rapidly evolving healthcare industry. Embracing technology and encouraging collaboration among educators, students, and healthcare facilities is critical for preparing students for best practices. Virtual reality, simulations, and online learning platforms enhance medical education, whereas interprofessional education encourages collaboration and mutual respect among healthcare professionals. Collaboration reduces inequities in medical education while ensuring high-quality learning experiences for all students. However, humanistic ideals must be prioritized, with instructors promoting compassion, understanding, and patient-centered care in learners. By embracing technology, collaboration, and humanistic values, we can better prepare future generations of healthcare providers to navigate modern medicine and offer high-quality care to patients globally.